Analysis of disease patterns and cost of treatments for prevention of deep venous thrombosis after total knee or hip replacement: results from the Practice Analysis of THromboprophylaxis after Orthopaedic Surgery (PATHOS) study - Degli Esposti L; Didoni G; Simon T; Buda S; Sangiorgi D; Degli Esposti E (Dove Medical Press, 2012)
Luca Degli Esposti,1 Guido Didoni,2 Teresa Simon,3 Stefano Buda,1 Diego Sangiorgi,1 Ezio Degli Esposti11CliCon Health, Economics and Outcomes Research, Ravenna, Italy; 2BMS Italy, Rome, Italy; 3BMS Global, Princeton, NJ, USAIntroduction: Venous thromboembolism (VTE) is a well-known complication of total hip replacement (THR) and total knee replacement (TKR). Various drugs have been introduced in an attempt to reduce the mortality as well as the short-term and long-term morbidity associated with the development of VTE. The aim of this study was to analyze drug utilization for thromboprophylaxis and the cost of illness in real clinical practice in patients with THR or TKR.Materials and methods: A multicenter, retrospective, observational cohort study based on local health unit administrative databases was conducted. All patients (≥18 years old) discharged for THR/TKR procedures between January 1, 2007 and December 31, 2008 were included in the study. The date of first hospital discharge was the index date; patients were followed up for a period of 12 months.Results: A total of 10,389 patients were included: 3516 males (33.8%, 69.4 ± 10.4 years) and 6873 females (66.2%, 71.7 ± 9.0 years), of which 5483 (52.8%) were discharged for THR and 4906 (47.2%) for TKR. First antithrombotic treatments after discharge were enoxaparin (3937, 37.9%), heparin (3752, 36.1%), antiplatelet agents (658, 6.3%), vitamin K antagonists (276, 2.7%), fondaparinux (136, 1.3%), combinations (185, 1.8%), and no therapy (1445, 13.9%). Overall, we observed 2347 (22.6%) treatment changes; median duration of antithrombotic treatment was 23 days (range 11–47) for THR and 22 days (range 11–46) for TKR. During the follow-up period, we observed 129 cases of VTE (120 per 10,000 patients), five post-thrombotic syndrome (4.8 per 10,000 patients), and three heparin-induced thrombocytopenia (2.9 per 10,000 patients). Median cost for both THR and TKR was €9052.00 (range €8063.00–€9084.96), with a median length of stay of 9.0 days (range 6.0–12.0).Keywords: venous thromboembolism, VTE, total hip replacement, THR, total knee replacement, TKR, real practice, cost of illness, antithrombotic therapy